AN INVESTIGATION INTO LOSS AND GAIN IN VIETNAMESE- ENGLISH TRANSLATIONAL VERSIONS OF TRINH CONG SON’S SONGS - Hồ Thị Hoài Nhân (Trường Đại học Ngoại ngữ, 2025)
This study aims at conducting the loss and gain in a series of Trinh Cong Son’s songs translated from Vietnamese into English. The data for analysis is taken from 100 Vietnamese songs and 100 English translational versions of Trinh Cong Son. The qualitative and quantitative approachs are exploited in order to help the researcher achieve the aims and objectives proposed. After studying the findings of thesis, we also recognize that due to the differences and varieties between the two languages, the loss and gain phenomenon is unavoidable. In particular, in many English translational songs of Trinh Cong Son, the gain and loss have happened so many times, especially in meaning and in structures. In addition, the loss at the rhetorical expressions manifested in the English translational songs has occurred frequently. Basing on what the research has found, it is very important to conclude that when translating the meaning from the source language to the target one, we should avoid the word- word translation. The communicative translation seems to be the most effective method we should apply for. Besides, the knowledge of cultural aspect in each language also has an influence on a better translation.